Sinergi untuk Negeri: Peran Strategis Administrasi dalam Koordinasi Logistik dan Tata Kelola Donasi Pasca Bencana di Pidie Jaya - BAHRI, SAMSUL; Nurliana, Nurliana (Seumike : Society Progress Journal, 2026)
The success of disaster management is significantly determined by administrative agility in managing limited resources amidst a crisis. This study aims to evaluate the strategic role of public administration in logistics coordination and donation governance following the earthquake in Pidie Jaya Regency. Using a descriptive qualitative approach, this research analyzes reporting mechanisms, data accuracy, and the effectiveness of inter-agency coordination. Data were gathered through policy document studies, agency performance reports, and observations of digital information systems. The results indicate that administrative strengthening through the innovation of the digital-based Post-Disaster Damage Data Inventory System (SIAP) improved reporting speed by 40%. However, the main challenge remains the synchronization of donation data from the private sector, which often bypasses formal channels without standard recording. The analysis of coordination effectiveness using dimensions of unity of action and communication shows results in the "Good" category with an index score of 0.72. This study concludes that orderly administration is the primary foundation for public accountability and efficient aid distribution. Practical suggestions include the standardization of operating procedures (SOP) for non-governmental donation reception and enhancing digital literacy among village-level officials.